Ground of specialized physical training of teacher of middle school - Kolumbet A.N (Kharkov National Pedagogical University, 2012)
Purpose of work - to expose important physical qualities of teacher, personal properties and psychophysiological qualities professionally. Also to expose requirement to motive preparedness of teachers. 674 teachers of middle schools of city of Kiev and Kiev area took part in an experiment. It is set that professional activity requires a display typical professionally the important personal qualities: communicability, of principle, tolerance, kindness, sympathy, empathy, eloquence. It is exposed that to professionally important physical qualities of teacher it is possible to take general and local (hands, feet, back, neck) static endurance, force of basic muscular groups and power endurance of hands, exactness and speed of motive reaction. It is well-proven that it is necessary to take to the most essential psychophysiological qualities: perception, memory, imagination, restraint, ability quickly to make a decision, ability to work in a nervous situation, ability expressly to execute the tasks in the conditions of emotional tension, good reaction. It is marked that an important role in mastering of profession and achievement of tops of professionalism is played by the use of values of physical education in providing of the proper health, physical and spiritual development, motive preparedness level.